2017
DOI: 10.1111/jcmm.13080
|View full text |Cite
|
Sign up to set email alerts
|

Circulating fibrocyte mobilization in negative pressure wound therapy

Abstract: Non-healing diabetic wounds are difficult to treat. They also create heavy financial burdens for both patients and society. Negative pressure wound therapy (NPWT) has been adopted to treat intractable wounds and has proved to be effective. However, the mechanisms that underlie the effects of this treatment are not entirely understood. Circulating fibrocytes are unique haematopoietic-derived stem cells that have been reported to play a pivotal role in wound healing. Here, we have investigated the effect of NPWT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…IL-4, in combination with GM-CSF, can further promote inflammation by increasing differentiation of monocytes into dendritic cells [ 44 ]. Bellini and colleagues also showed that IL-4 can stimulate a unique circulating leukocyte subpopulation (0.1–0.5%) of bone marrow-derived stem cells known as fibrocytes that leave the blood and enter the site of healing and differentiate into fibroblasts/myofibroblasts with increased production of cell matrix components, growth factors, and inflammatory cytokines [ 45 47 ]. Therefore, in the current study, it is possible that IL-4 contributes to a heightened systemic inflammatory response observed in TXA patients (Figs 3 , 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL-4, in combination with GM-CSF, can further promote inflammation by increasing differentiation of monocytes into dendritic cells [ 44 ]. Bellini and colleagues also showed that IL-4 can stimulate a unique circulating leukocyte subpopulation (0.1–0.5%) of bone marrow-derived stem cells known as fibrocytes that leave the blood and enter the site of healing and differentiate into fibroblasts/myofibroblasts with increased production of cell matrix components, growth factors, and inflammatory cytokines [ 45 47 ]. Therefore, in the current study, it is possible that IL-4 contributes to a heightened systemic inflammatory response observed in TXA patients (Figs 3 , 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis has proposed that NPWT acts through alteration in the gene expression profile. This has been supported in animal models and preliminarily in humans [ 7 13 ], however, has never been systematically examined.…”
Section: Introductionmentioning
confidence: 99%
“…Collagen production and cell migration are also induced [9]. The latest data show that NPWT leads to the accumulation of circulating fibrocytes in wounds as well [4]. This paper demonstrates that the NPWT can additionally induce a systemic effect.…”
Section: Mechanism Of Action Of Npwtmentioning
confidence: 71%